UPAYA PEMULIHAN TERHADAP EMOSI KORBAN TINDAK PIDANA PEDOFILIA (STUDI KASUS DI UNIT PELAKSANA TEKNIS PERLINDUNGAN PEREMPUAN DAN ANAK (UPT PPA) PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) PROVINSI RIAU) - Kholiq , Azmi; Tutrianto, Rio (Sisi Lain Realita, 2024)
Human Rights (HAM) in all aspects of life, especially the protection of children in Indonesia. It is explained in the law that children are an inseparable part of the survival of human life and the sustainability of a nation and state. The rise in recent years how vulnerable children are to become victims of immoral crimes. A crime against decency is defined as a form of violation/crime against moral values ​​(moral norms). Pedophilia is a form of crime against children. Pedophilia is someone who has deviant sexual behavior with children, Pedophilia is a disorder or mental disorder in someone to act by making children the target of that action, generally the form of action is in the form of an outlet for sexual desire. This act of sexual harassment is very disturbing because the victims themselves are children, this sexual harassment causes psychological trauma that cannot be cured in a short time. Based on the facts that happened, this study aims to determine the efforts to recover the emotions of children who are victims of pedophilia crime at UPT PPA Riau Province. This type of research is descriptive qualitative using qualitative methods. namely descriptive research. The most practical way to do this is to conduct in-depth interviews. In this study, the authors made key informants and informants the object of research. Because by conducting interviews with key informants and informants to get answers from the results of related research, efforts to handle child victims of sexual harassment, the Technical Service Unit of the Service (UPT PPA) Center for the Protection of Women and Children Empowerment (UPT PPA) obtained the following results: loss of minor trauma due to sexual harassment, improved social function and better communication in the family and in the environment. The technique used in trauma recovery is to build a relationship with the victim, so that the victim is more flexible and confident in conveying what he wants to tell